2013
DOI: 10.1021/je400811h
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Determination of Interfacial Tension and Miscibility of the CO2–Crude Oil System; Temperature, Pressure, and Composition Effects

Abstract: Interfacial tension (IFT) as one of the main properties for efficient CO2 flooding planning in oil reservoirs depends strongly on pressure, temperature, and composition of the reservoir fluids. Therefore, it is important to measure this property at real reservoir conditions for successful field development plan. In this study, an axisymmetric drop shape analysis (ADSA) has been utilized to measure the equilibrium IFTs between crude oil and CO2 at different temperatures and pressures. Moreover, minimum miscibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
106
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 162 publications
(115 citation statements)
references
References 59 publications
(111 reference statements)
9
106
0
Order By: Relevance
“…This different effect is due to the accumulation of colloidal particles at the interface of the two phases. In general, the composition of the gas phase and heavy components of crude oil is two key factors that can likely affect FCMP (Gu et al 2013;Hemmati-Sarapardeh et al 2013). Several researchers have also demonstrated that the pressure of miscibility conditions of the crude oil-CH 4 system is higher than that for the crude oil-CO 2 system (Kazemzadeh et al 2015;Tathed et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…This different effect is due to the accumulation of colloidal particles at the interface of the two phases. In general, the composition of the gas phase and heavy components of crude oil is two key factors that can likely affect FCMP (Gu et al 2013;Hemmati-Sarapardeh et al 2013). Several researchers have also demonstrated that the pressure of miscibility conditions of the crude oil-CH 4 system is higher than that for the crude oil-CO 2 system (Kazemzadeh et al 2015;Tathed et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Among enhanced oil recovery (EOR) methods, CO 2 injection has gained much popularity due to its considerable effect on oil recovery enhancement and reducing the amount of greenhouse gas emissions by its sequestration in depleted oil reservoirs [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods for IFT measurements have been proposed in the literature such as capillary rise, Wilhelmy plate, maximum bubble pressure, drop weight, sessile drop, spinning drop and pendant drop (Zolghadr et al, 2013a;Hemmati-Sarapardeh et al, 2014;Andreas et al, 1938;Winkel, 1965). Among these methods, the sessile and pendant drop analyses are reported to be consistent and more reliable at high pressure and high temperature (HPHT) conditions, which may be encountered during oil recovery (Winkel, 1965;Rotenberg et al, 1982).…”
Section: Introductionmentioning
confidence: 99%